Construction of a framework for the analysis of experiences in participatory mapping. Comparison of two social organizations in Latin America - Oliveras González, Xavier (2022)
The essay seeks to contribute to the understanding of participatory mapping, a methodology used to reflect on and represent the territory based on the territorial and social communities’ knowledge and participation. For this, firstly, a framework is built for the comparative analysis of the experiences of participatory mapping, which is based on four categories (the participating actors, the production process, the purpose, and the result). Secondly, that analytical framework is applied to two social organizations in Latin America: Iconoclasistas, in Argentina, and CACAO, in Mexico. Both groups have a formal organization, a vast trajectory, and digital presence. For their analysis, a documentary review of their web pages and publications (including maps and other materials) were carried out. The results allow us to conclude that the proposed analytical framework is functional.